2015
DOI: 10.1515/bvip-2015-0048
|View full text |Cite
|
Sign up to set email alerts
|

Selected biochemical and oxidative stress parameters and ceruloplasmin as acute phase protein associated with bovine leukaemia virus infection in dairy cows

Abstract: The aim of this study was to determine the ceruloplasmin (Cp) and vitamin C concentrations, the total antioxidant status (TAS), and selected biochemical parameters in dairy cows spontaneously infected with bovine leukaemia virus (BLV). Of the 27 cows included in the study, 18 animals were seropositive for enzootic bovine leukosis (EBL), whereas nine cows were seronegative and were used as controls. The serum aspartate aminotransferase (AST) (P = 0.003) and Cp concentrations (P = 0.03) decreased (65.17 ± 5.03 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
2
5
2
2
Order By: Relevance
“…In this study, serum hp, Saa and Cp concentrations were determined in the animals in the control group (table 2) while these values were seen to be within the scope of the limits indicated for healthy cattle by other researchers (AKALIN et al, 2015;AYTEKIN et al, 2016;BASBUG et al, 2016;CHAN et al, 2004;ECKERSALL and CONNER, 1988;HUSSEIN et al, 2012;NAZIFI et al, 2009;NISBET et al, 2008;SKINNER, 2001;ULUTAS et al, 2011).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In this study, serum hp, Saa and Cp concentrations were determined in the animals in the control group (table 2) while these values were seen to be within the scope of the limits indicated for healthy cattle by other researchers (AKALIN et al, 2015;AYTEKIN et al, 2016;BASBUG et al, 2016;CHAN et al, 2004;ECKERSALL and CONNER, 1988;HUSSEIN et al, 2012;NAZIFI et al, 2009;NISBET et al, 2008;SKINNER, 2001;ULUTAS et al, 2011).…”
Section: Discussionsupporting
confidence: 68%
“…also, an important correlation was detected between the clinical appearance of the disease and hp and Saa. akaLIN et al (2015) reported that Cp levels decreased in dairy cattle infected with bovine leukemia virus and this affected Cp synthesis of bovine leukemia virus, or it might suppress Cp secretion in the liver due to an unknown mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement and evaluation of the biochemical profile may be helpful in elucidating the pathogenesis and prognosis of the disease. Significant changes occur in the blood biochemical parameters of the animals exposed to viral diseases [ 31 – 33 ]. It has been reported that elevated serum cardiac troponin I is associated with myocardial injury during foot-and-mouth disease virus infection [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…zakażenie wirusem opryszczki bydła (BoHV-1) (16). Z kolei infekcja wirusem białaczki bydła istotnie obniża stężenie AST, bez wpływu na poziom LDH (1).…”
Section: Wyniki I Omówienieunclassified
“…Z dostępnej literatury (1,18,48) wynika, że system utrzymania, pora roku, poziom laktacji czy nawet stan zdrowotny wywierają na ogół niewielki wpływ na koncentrację makroelementów w surowicy krwi krów. Wydaje się, że koncentracja głównych makroskładników w surowicy może ulegać niekorzystnym fizjologicznie zmianom, gdy niezbilansowany jest poziom żywienia mineralnego, np.…”
Section: Wyniki I Omówienieunclassified